MODERN METHODS OF ORGANIZING FOREIGN LANGUAGES LESSONS - Pardayeva Aziza; Normurodov Afro'zbek (Journal Park Publishing, 2023)
This article delves into the contemporary landscape of organizing foreign language lessons, exploring the latest teaching methods that have emerged in response to advancements in education and technology. Through a thorough literature analysis, the article investigates the effectiveness of various methods, focusing on the communicative approach and technology-enhanced learning. The methods section outlines practical strategies for implementing these approaches, and the results section discusses their impact on student engagement and language proficiency. The discussion section critically analyzes the findings, highlighting strengths and limitations, leading to conclusive suggestions for optimizing foreign language lessons in the modern era.
Keywords: Student’s interests, listening, comprehension, instructional strategies, conducting research, beginner level grammar, mistakes, communication, native atmosphere.